Pengaruh Budaya Organisasi terhadap Produktivitas Karyawan pada PT. Dome Semanggi - Indah Pangesti; Heppy Atma Pratiwi (Departement of Mathematics Education, 2022)
The goal of this research was to see how organizational culture impacts employee productivity. The data for this study was collected using a questionnaire that was given to 30 respondents. This gives us a sample size of 30 people. The sampling technique used is random sampling, which is obtained by using the Slovin formula for calculation. Data analysis uses a variety of statistical techniques to test the validity and reliability of data, as well as to examine relationships between different variables. These techniques include tests such as the F test, t test and coefficient of determination. The results of the analysis showed that organizational culture has a positive and significant effect on job satisfaction and work productivity. Job stress also has a positive and significant effect on job satisfaction. A partial test of organizational culture has shown that it significantly affects work productivity. Employee productivity is influenced by a number of factors, including other factors that have an impact on productivity.